2012
DOI: 10.1371/journal.pone.0050465
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Di-(2-ethylhexyl)-phthalate Exposure on Fertilization and Embryonic Development In Vitro and Testicular Genomic Mutation In Vivo

Abstract: The present study was undertaken to determine the reproductive hazards of Di-(2-ethylhexyl)-phthalate (DEHP) on mouse spermatozoa and embryos in vitro and genomic changes in vivo. Direct low-level DEHP exposure (1 μg/ml) on spermatozoa and embryos was investigated by in vitro fertilization (IVF) process, culture of preimplanted embryos in DEHP-supplemented medium and embryo transfer to achieve full term development. Big Blue® transgenic mouse model was employed to evaluate the mutagenesis of testicular genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
2
19
1
1
Order By: Relevance
“…Treatment groups included a vehicle control (methanol) and each of five EDCs at environmentally relevant doses [10 nM BPA (36 nM fetal serum, [35]), 5 μM DEHP (7.7μM pubertal serum, [12]), 30 μM ATR (up to 7 μM drinking water reported, [36]), 100 nM PFOA (average 94 nM ≥12 year old serum, [37]), and 25 nM TBT (0.17 – 534 adult nM serum, [38]). These concentrations are within the range those reported for human serum, for drinking water, or studies reported for mammalian oocytes and preimplantation stage embryos or pluripotent cells in vitro [22, 23, 27, 3941]. The concentration of ATR used was ~4-fold higher than the maximum concentration reported in one study in drinking water [36], and one study of occupational human serum level (up to 245 nM [42]).…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…Treatment groups included a vehicle control (methanol) and each of five EDCs at environmentally relevant doses [10 nM BPA (36 nM fetal serum, [35]), 5 μM DEHP (7.7μM pubertal serum, [12]), 30 μM ATR (up to 7 μM drinking water reported, [36]), 100 nM PFOA (average 94 nM ≥12 year old serum, [37]), and 25 nM TBT (0.17 – 534 adult nM serum, [38]). These concentrations are within the range those reported for human serum, for drinking water, or studies reported for mammalian oocytes and preimplantation stage embryos or pluripotent cells in vitro [22, 23, 27, 3941]. The concentration of ATR used was ~4-fold higher than the maximum concentration reported in one study in drinking water [36], and one study of occupational human serum level (up to 245 nM [42]).…”
Section: Methodssupporting
confidence: 55%
“…Consequently, although rodent stem cell and rodent developmental studies provide important information about the potential developmental consequences of EDC exposure, the possibility of species differences needs to be addressed by determining EDC effects in model organisms more closely resembling humans. Some other studies reported that some EDCs affect germ cells and early embryos, but others reported little or no effect [2232]. Recent studies also illustrate the effects of prolonged low-level exposure on embryonic stem cell (ESC) differentiation [33].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that DEHP inhibited DNA replication and induced cellular oxidative stress is reminiscent of previous work suggesting that DEHP treatment may induce DNA damage303132. Synthesis and conjugation of poly(ADP-ribose) polymers (PARs) to proteins are common response to DNA damage.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, an increased expression of LXRα and its downstream genes involved in lipid and cholesterol synthesis was observed in both male and female gonads [9]. Treatment of Big Blue ® transgenic mice with DEHP for 4 weeks induced a 3-fold increase in genomic DNA mutation frequency [10]. Furthermore, a 96 h exposure to 10 μM MEHP of cultured chicken postnatal testis cells altered seminiferous tubule differentiation [11].…”
Section: Introductionmentioning
confidence: 99%